CoQ10 Augments Rosuvastatin Neuroprotective Effect in a Model of Global Ischemia via Inhibition of NF-κB/JNK3/Bax and Activation of Akt/FOXO3A/Bim Cues - Abd El-Aal, Sarah A.; Abd El-Fattah, Mai A.; El-Abhar, Hanan S. (Frontiers in Pharmacology, 2017)
Statins were reported to lower the CoQ10 content upon their inhibition of HMG-CoA reductase enzyme and both are known to possess neuroprotective potentials; therefore, the aim is to assess the possible use of CoQ10 as an adds-on therapy to rosuvastatin to improve its effect using global I/R model. Rats were allocated into sham, I/R, rosuvastatin (10 mg/kg), CoQ10 (10mg/kg) and their combination. Drugs were administered orally for 7 days before I/R. Pretreatment with rosuvastatin and/or CoQ10 inhibited the hippocampal content of MDA, NO and boosted GSH and SOD. They also opposed the up-regulation of gp91phox, and p47phox subunits of NADPH oxidase. Meanwhile, both agents reduced content/expression of TNF-α, iNOS, NF-κBp65, ICAM-1 and MPO. Besides, all regimens abated cytochrome c, caspase-3 and Bax, but increased Bcl-2 in favor of cell survival. On the molecular level, they increased p-Akt and its downstream target p-FOXO3A, with the inhibition of the nuclear content of FOXO3A to downregulate the expression of Bim, a pro-apoptotic gene. Additionally, both treatments downregulate the JNK3/c-Jun signaling pathway. The effect of the combination regimen overrides that of either treatment alone. These effects were reflected on the alleviation of the hippocampal damage in CA1 region inflicted by I/R. Together, these findings accentuate the neuroprotective potentials of both treatments against global I/R by virtue of their rigorous multi-pronged actions, including suppression of hippocampal oxidative stress, inflammation, and apoptosis with the involvement of the Akt/FOXO3A/Bim and JNK3/c-Jun/Bax signaling pathways. The study also nominates CoQ10 as an adds-on therapy with statins.